Application of PBL-STEAM Based on Mandai Local Wisdom to Students' Critical Thinking Skills on Osmosis Pressure Material - Rahmadani, Fitri Nur; Erika*, Farah; Watulingas, Maasje Catherine; Kasyfita, Nurul (Jurnal Pendidikan Sains Indonesia, 2025)
The PBL-STEAM approach based on Mandai local wisdom is designed to encourage students' activeness and curiosity in solving real problems by integrating Mandai local wisdom values. This study aims to determine the effect of PBL-STEAM based on Mandai local wisdom on students' critical thinking skills (CTS) on osmosis pressure material. The research used a quasi-experimental method with a non-randomized pretest-posttest control group design. The study population was class XII students of SMA Negeri 2 Samarinda in the 2024/2025 school year, with a research sample of class XII-C as the experimental class and XII-D as the control class, totaling 68 students selected using purposive sampling. Data were collected through CTS tests, teacher and student activity observation sheets, and student response questionnaires. The average score for CTS of experimental class students was 79.56, with a high category, and the control class's score was 70.38, with a medium category. The results of the independent samples t-test showed a sig value. (2-tailed) 0.000 0.05, indicating a significant effect of PBL-STEAM based on Mandai local wisdom on students' CTS. The paired samples t-test results showed a sig value. (2-tailed) 0.000 0.05, indicating an increase in the learning outcomes of experimental class students. Teacher and student activities in the experimental class in learning each reached 100% of the very applied category and 90.82% of the outstanding category. The average student response to PBL-STEAM learning was 85.47%, which is included in the very good category, which proves that this learning based on Mandai local wisdom is able to improve students' CTS